An open‐channel flume study of flow characteristics through a combined layer of submerged and emerged flexible vegetation. Issue 2 (24th April 2013) - Li, Yiping; Anim, Desmond Ofosu; Wang, Ying; Tang, Chunyan; Du, Wei; Yu, Zhongbo; Acharya, Kumud
ABSTRACT Flowing water bodies often have plants that differ greatly in size and type, which interfere with fluid flow structure. Although there are studies describing vegetation–flow interactions in ideal laboratory conditions, their practical application is sometimes still difficult. This paper presents results of research involving laboratory simulations channel flow and the effects upon its structure as it passes through a combined layer of submerged and emerged vegetation in an open‐channel flume. Instantaneous time‐average velocity and turbulence at various locations were measured with a 3D acoustic Doppler velocimeter. The experimental results showed that the mean velocity profiles can be divided into three layers: bottom, middle and upper. The velocity profiles show the flow structure was complex variable over time creating mixing velocity layers associated with inflection points and velocity spikes. Turbulence intensity urms, vrms, wrms was nearly invariant for the flow depth at the bottom layer in most locations within the vegetation area. Maximum turbulence intensity occurred within the middle layer and migrated vertically as frontal width of the plant increased. Maximum turbulence intensity fluctuated at the velocity mixing layer where there is significant momentum exchange. The Manning's vegetation roughness coefficient n(v) due to vegetation resistance increased with vegetation density as expected. In all, the results show flow structure varies substantially at the stem section and at the canopy top of submerged vegetation. These analytical findings will be useful in understanding river channel hydraulic transport and mixing processes and useful in river engineering applications and modelling. Copyright © 2013 John Wiley & Sons, Ltd.